SUFFERING IN WESTERN ART: THREE TRANSFORMATIONS - Yvonne Korshak, (Journal of Dharma, 2020)
The suffering resulting from transgression is represented in some important instances by Greek visual artists, and the young girl falling to her knees as she vainly tries to pluck an arrow from her back is an example (PI: 1). She is a daughter of Niobe, a woman fortunate in the number of her children, having six sons and six daughters.